Interobserver Reliability of the Chest Radiograph in Pulmonary Embolism. (March 2014) - Sverzellati, Nicola; De Filippo, Massimo; Quintavalla, Marta; Randi, Giorgia; Franco, Fabio; Cobelli, Rocco; Valentino, Massimo; Rossi, Cristina; Colombi, Davide; Zompatori, Maurizio
This study was sought to evaluate the interobserver agreement for interpreting the chest radiograph of patients with suspected acute pulmonary embolism (PE). The chest radiographs of 300 patients with clinically suspected acute PE were reviewed by 4 radiologists. Observers assessed the chest radiographic abnormalities and classified the chest radiograph as normal or abnormal. We found that the overall interobserver agreement was good for the exclusion of any pleural or parenchymal abnormality (k = 0.6; 95% CI: 0.56-0.64) but fair (k = 0.28; 95% CI: 0.17-0.40) between junior radiologists when evaluating supine chest radiographs. The level of interobserver agreement for the interpretation of the chest radiograph as consistent or not with PE was fair (k = 0.24; 95% CI: 0.19-0.29), regardless of the observer experience. In conclusion, chest radiography may be reliably used for targeting patients with suspected acute PE for different subsequent diagnostic investigations.